2011
DOI: 10.1007/s11701-010-0220-0
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for robotic thyroidectomy: “the daVinci gasless single-incision axillary approach”

Abstract: Robotic thyroidectomy has been recently introduced as a new modality of treatment for selected benign and malignant thyroid lesions. The standard technique, popularized by a leading Korean group, combines an axillary and a thoracic approach to accomplish thyroid resection without neck incision. We recently introduced a modified technique that has enabled us to complete robotic thyroidectomy through a single axillary incision. We herein report our initial successful experience in 35 cases with the modified tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Table 2 reports the characteristics and demographics of the included studies. 11 articles were prospective cohort studies, [15][16][17][18][19][20][21][22][23][24][25] one was a prospective case-control study 26 and one was a randomized controlled trial, RCT. 27 Four studies were performed in Europe (Great Britain, Greece, Italy, and Romania), four in the United States of America, and five in Asia (China, n = 2, and South Korea, n = 3).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 reports the characteristics and demographics of the included studies. 11 articles were prospective cohort studies, [15][16][17][18][19][20][21][22][23][24][25] one was a prospective case-control study 26 and one was a randomized controlled trial, RCT. 27 Four studies were performed in Europe (Great Britain, Greece, Italy, and Romania), four in the United States of America, and five in Asia (China, n = 2, and South Korea, n = 3).…”
Section: Search Resultsmentioning
confidence: 99%
“…Each study employed a specific RATS approach and no intra‐study comparison for RATS approaches was available. Two studies 15 , 25 reported a total of 4 conversions into open procedures, all occurring during TGA total thyroidectomies. One conversion was due to excessive bleeding in a female patient, another one was due to unexpected high glandular volume (multinodular goitre) and two were due to previously undetected significant tumour extension (specifically, a papillary cancer invading the cricothyroid area and a follicular carcinoma with cranial extension).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trans axillary thyroidectomy poses the risk of brachial plexus injury due to arm position, thus in our case series we compared two arm positions. For the first four cases we used overhead arm position and for the last three cases we fixed the arm at 90°as used by Rodriguez et al [12]. In their case series of 338 patients Kang et al reported one case of brachial plexus injury and Landry et al [13] in their case series of 14 patients reported 2 patients with brachial plexus injury.…”
Section: Discussionmentioning
confidence: 99%